Lord’s Land God’s Land: A Messianism-Based Social Movement in the Dutch East Indies Through a Historical Ecological View - Munigar, Muhammad Miqdad Rojab; Mahzuni, Dade (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
This article explores the configuration of messianic social movements in the Dutch East Indies through a historical ecological lens. Using historical methodology combined with ecological analysis, the study examines how environmental degradation and restricted access to land and water contributed to the emergence of resistance movements such as the Samin Movement, the Ratu Pelabuhan Rebellion, and the Gedangan Incident. These movements are interpreted not merely as political defiance, but as ecological responses to exploitative colonial policies. Figures like Samin Surosentiko, Rachman, and Kiai Hasan functioned as spiritual leaders whose legitimacy was rooted in local cosmologies and ecological justice. This research addresses ontological issues concerning the human-nature relationship, epistemological challenges in rereading colonial archives, and axiological commitments to the rights of indigenous communities. The study contributes to historical scholarship by offering a novel perspective that emphasizes environmental and spiritual dimensions of resistance, suggesting that messianic movements in the colony were deeply grounded in local ecological worldviews.